The Value of Liver and Spleen Stiffness for Evaluation of Portal Hypertension in Compensated Cirrhosis. Issue 5 (14th December 2021) - Reiberger, Thomas
Abstract : Patients with compensated advanced chronic liver disease who develop clinically significant portal hypertension (CSPH) are at high risk for hepatic decompensation and mortality if left untreated. Liver biopsy and hepatic venous pressure gradient (HVPG) measurements are the current gold standard procedures for determining fibrosis severity and diagnosing CSPH, respectively; however, both are invasive, limiting their use in clinical practice and larger trials of novel agents. As such, there is an unmet clinical need for reliable, validated, noninvasive measures to detect CSPH and to further assess portal hypertension (PH) severity. Alterations in the biomechanical properties of the liver or spleen in patients with cirrhosis can be quantified by tissue elastography, which examines the elastic behavior of tissue after a force has been applied. A variety of methods are available, including magnetic resonance elastography, shear‐wave elastography, and the most thoroughly investigated measure, vibration‐controlled transient elastography. Liver stiffness (LS) and spleen stiffness (SS) measurements offer valuable alternatives to detect and monitor CSPH. Both LS and SS correlate well with HVPG, with thresholds of LS >20‐25 kPa and SS >40‐45 kPa indicating a high likelihood of CSPH. Because SS is a direct and dynamic surrogate of portal pressure, it has the potential to monitor PH severity and assess PH improvement as a surrogate marker for clinical outcomes. Importantly, SS seems to be superior to LS for monitoring treatment response in clinical trials focusing on reducing PH. Abstract : Patients with compensated advanced chronic liver disease may develop portal hypertension that indicates high risk for progression to decompensated cirrhosis. Elastography of the liver and the spleen may overcome the limitation of the invasive gold‐standard for assessing severity of portal hypertension, which is hepatic venous pressure gradient. We present the current evidence supporting liver stiffness and spleen stiffness as valuable non‐invasive tools for the assessment of portal hypertension in patients with compensated liver cirhosis.image